Organotrialkoxysilane mediated rapid and controlled synthesis metal nanoparticles in both homogeneous and heterogeneous phase and their catalytic applications - Pandey P.C.; Mitra M.; Pandey A.K.; Narayan R.J. (My University, 2025)
Abstract: Organotrialkoxysilanesilane (e.g., 3-glycidoxypropyltrimethoxysilane-3-GPTMS, 3-aminopropyl trimethoxysilane-3-APTMS) mediated synthesis of noble metal nanoparticles (AuNPs, AgNPs) and their multimetallic analogues (Au–Ag bimetallic and Au–Ag–Pd trimetallic nanoparticles) over short durations (5–120 s) is reported. These functional alkoxysilanes are microwave active, allowing a significant reduction in time for nanoparticle synthesis with high stability for practical applications. The process also enables incorporation of noble metal nanoparticles within silica nanoparticles. Examples of AuNP, PdNPs, and Pd–Ni bimetallic within mesoporous silica nanoparticles are reported. The catalytic activity of these nanoparticles and their multimetallic analogues for organic dye degradation was evaluated. Synergistic interactions in bimetallic and trimetallic nanoparticles promote rapid degradation of methylene blue. A comparison of the catalytic activity of monometallic noble metal nanoparticles and their multimetallic analogues on methylene blue degradation is reported herein. Graphic Abstract: [Figure not available: see fulltext.] © 2021, The Author(s), under exclusive licence to The Materials Research Society.